Urinary tract infections and antibiotic use in pregnancy - qualitative analysis of online forum content - Flavia Ghouri; Amelia Hollywood; Kath Ryan (BMC, 2019)
Abstract Background Antibiotics are standard treatment for asymptomatic and symptomatic urinary tract infections (UTIs) in pregnancy. Their overuse, however, can contribute to antimicrobial resistance (AMR) and expose the foetus to drugs that might affect its development. Preventative behaviours are currently the best option to reduce incidences of UTIs and to avoid the use of antibiotics in pregnancy. The aim of this study was to explore women's experiences of UTIs in pregnancy to develop an understanding of their concerns and to optimise and encourage behaviours that facilitate appropriate use of antibiotics. Methods An online pregnancy forum in the United Kingdom (UK) was used to collect data on women's discussions of UTIs. A total of 202 individual threads generated by 675 different usernames were selected for analysis. The data was organised using NVivo 11® software and then analysed qualitatively using inductive thematic analysis. Results Women's perceptions of UTIs and antibiotic use in pregnancy were driven by their pre-natal attachment to the foetus. UTIs were thought to be common and high risk in pregnancy, which meant that antibiotics were viewed as essential in the presence of suspected symptoms. The dominant view about antibiotics was that their use was safe and of little concern in pregnancy. Women reported an emotional reaction to developing a UTI. They coped by seeking information about behaviour change strategies to assist with recovery and through emotional support from the online forum. Conclusions Women face dual risks when they experience UTIs; the risk from the infection and the risk from antibiotic treatment. Pre-natal attachment to the foetus is highlighted in the decision making process. The focus is on the shorter term risk from UTIs while undermining the longer term risks from antibiotic use, especially the risk of AMR. A balanced view needs to be presented, and evidence-based infection prevention strategies should be promoted, to women to ensure appropriate antibiotic use in pregnancy, to address the global challenge of AMR.